Newspaper Reading Habits at University of Agricultural Sciences (UAS) Bangalore - A Case Study - Naika, B. M. Puneeth; K. Venkataranga; N. Kavya; M.Papegowda; M. R. Reshma (Journal of Agricultural Extension Management, 2021)
Newspapers are the best vehicles to spread information to the grassroots level. Newspapers provide current information on social, econicms, political, academic, cultural, crime, sports etc. They are treated as primary source of information with facts and reliability. This paper examines the newspapaer and e-newspapaer clipping reading habits of users of UAS Library.